Changing prioritization for transplantation: MELD-Na, hepatocellular carcinoma exceptions, and more. Issue 2 (April 2016) - Kalra, Avash; Wedd, Joel P.; Biggins, Scott W.
Abstract : Purpose of review: This article summarizes the landmark events that shaped current deceased donor liver allocation and distribution policy in the USA and to provide an update on recently approved and anticipated policy changes. Recent findings: For liver transplant candidates with model for end-stage liver disease more than 11, the 'MELD-Na' equation incorporating serum sodium will be used for allocation starting January 2016. The 'delay and cap' policy for hepatocellular carcinoma delays the start of model for end-stage liver disease exception by 6 months and subsequently grants 28 points, with increases every 3 months thereafter up to a maximum score at 34 points. There is new guidance for exception petitions for neuroendocrine tumors, polycystic liver disease, and primary sclerosing cholangitis. New guidelines for selecting candidates for simultaneous liver-kidney transplant are being developed that may include a 'safety net' for liver-only recipients with posttransplant renal failure. In an effort to provide broader geographic sharing of livers than in the current distribution system, new larger geographic areas are being considered. Summary: Recent policy changes were designed to reduce waitlist mortality, yet inclusion of outcomes measures in allocation and the use of larger geographic distribution units will likely guide future policy changes.